A comparative study of K-rich and Na/Ca-rich feldspar ice-nucleating particles in a nanoliter droplet freezing assay - Peckhaus, Andreas; Kiselev, Alexei; Hiron, Thibault; Ebert, Martin; Leisner, Thomas (Atmospheric chemistry and physics, 2016)
Abstract. A recently designed droplet freezing assay was used to study the freezing of up to 1500 identical 0.2nL water droplets containing suspensions of one Na/Ca-rich feldspar and three K-rich and one Na/Ca-rich feldspar particles. Three types of experiments have been conducted: cooling ramp, isothermal freezing at a constant temperature, and freeze–thaw cycles. The observed freezing behavior has been interpreted with the help of a model based on the classical nucleation theory (soccer ball model (SBM); Niedermeier et al., 2015). By applying the model to the different freezing experiments conducted with the same ice-nucleating material, the unique sets of model parameters for specific feldspar suspensions could be derived. The SBM was shown to adequately describe the observed cooling rate dependence, the ice-nucleating active sites (INAS) surface density ns(T) in a wide temperature range, and the shift of the freezing curves towards lower temperature with dilution. Moreover, the SBM was capable of reproducing the variation of INAS surface density ns(T) with concentration of ice-nucleating particles in the suspension droplets and correctly predicting the leveling-off of ns(T) at low temperature. The freeze–thaw experiments have clearly shown that the heterogeneous freezing induced even by very active ice-nucleating species still possesses a stochastic nature, with the degree of randomness increasing towards homogeneous nucleation.
Published: 15 September 2016